1984
DOI: 10.1203/00006450-198409000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Thromboxane Production between Neonatal and Adult Platelets in Response to Arachidonic Acid and Epinephrine

Abstract: SummaryIn this study, we have investigated the possible role of the proaggregatory arachidonic acid (AA) metabolite thromboxane, in the impaired function of neonatal platelets. In platelet-rich plasma thromboxane production (measured by radioimmunoassay of thromboxane B2) was not different between neonates and adults when stimulated by thrombin (at 0.1 or 1.0 U/ml) or collagen (70 pg/ml) although neonatal platelets produced decreased thromboxane (TBXZ) postepinephrine stimulation. In response to 1 U/ml thrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Early studies demonstrated that cord blood-derived neonatal platelets release more arachidonic acid in response to thrombin when compared with adult platelets, however the cord blood platelets synthesized less TxB 2 (7). Subsequent studies have failed to find a difference in cord blood-derived neonatal platelet TxB 2 generation in response to thrombin and collagen when compared to adult platelet TxB 2 generation (8). In platelet-rich plasma, cord blood-derived neonatal platelets produced a greater amount of TxB 2 as compared to adult platelets in response to arachidonic acid (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies demonstrated that cord blood-derived neonatal platelets release more arachidonic acid in response to thrombin when compared with adult platelets, however the cord blood platelets synthesized less TxB 2 (7). Subsequent studies have failed to find a difference in cord blood-derived neonatal platelet TxB 2 generation in response to thrombin and collagen when compared to adult platelet TxB 2 generation (8). In platelet-rich plasma, cord blood-derived neonatal platelets produced a greater amount of TxB 2 as compared to adult platelets in response to arachidonic acid (8).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have failed to find a difference in cord blood-derived neonatal platelet TxB 2 generation in response to thrombin and collagen when compared to adult platelet TxB 2 generation (8). In platelet-rich plasma, cord blood-derived neonatal platelets produced a greater amount of TxB 2 as compared to adult platelets in response to arachidonic acid (8). This difference reversed after platelet washing, suggesting that factors present in the plasma may account for this difference (8).…”
Section: Introductionmentioning
confidence: 99%
“…Stuart and Allen (37) and Stuart et al (38) have identified some differences in AA release and TxA2 synthesis between adult and neonatal platelets. In response to maximal stimulation by thrombin, neonatal platelet membranes release more AA than those of the adult.…”
Section: Adult (Mfi)mentioning
confidence: 99%
“…The percentage of free fatty acid comprising AA is also signifi cantly higher in infant cord blood than in maternal blood [26,27], Thus in the prema ture infant, a combination of various factors may contribute towards decreasing the AA binding capacity of plasma, with a resultant increase in the production of vasoactive compounds using AA as substrate. Previous measurements from our laboratory of thromboxane B2 generation in platelet-rich plasma from the neonate has demonstrated increased thromboxane production in re sponse to low-dose exogenous AA when compared to the adult [28]. The differences in thromboxane generation between plate lets from the adult versus neonate were abol ished however in a washed platelet system suggesting that the effect was plasma related [28].…”
Section: Discussionmentioning
confidence: 77%
“…Previous measurements from our laboratory of thromboxane B2 generation in platelet-rich plasma from the neonate has demonstrated increased thromboxane production in re sponse to low-dose exogenous AA when compared to the adult [28]. The differences in thromboxane generation between plate lets from the adult versus neonate were abol ished however in a washed platelet system suggesting that the effect was plasma related [28]. This previous demonstration of in creased production of a vasoconstrictor and proaggregatory metabolite in the neonate, coupled with our present work describing differences in arachidonic binding to plasma especially in the premature infant at risk, suggests that this latter finding is not only of theoretical interest, but may have practical implications in the care of the neonate.…”
Section: Discussionmentioning
confidence: 99%